2020
DOI: 10.3390/plants9020165
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity Analysis of Italian Lolium spp. to Glyphosate in Agricultural Environments

Abstract: Empirical observations generally indicate a shifting and decreased Lolium spp. susceptibility to glyphosate in Italy. This is likely due to the long history of glyphosate use and to the sub-lethal doses commonly used. There is, therefore, a need to determine the variability of response of Lolium spp. to glyphosate and identify the optimum field dose. To perform a sensitivity analysis on Lolium spp. populations in an agriculture area, collection sites were mainly chosen where glyphosate had not been applied int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…The similarity of their responses could be due to the low concentrations of glyphosate that were used here. Previous studies that have reported intraspecific variation in plant tolerance to glyphosate have usually examined direct responses to herbicide application based on dose-response bioassays (e.g., Barroso et al 2010;Panozzo et al 2020), in which plants are typically exposed to much higher concentrations of glyphosate than those used here. Overall, our results support the previous finding that plants may be less sensitive to glyphosate residues than their associated micro-organisms (Claassens et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The similarity of their responses could be due to the low concentrations of glyphosate that were used here. Previous studies that have reported intraspecific variation in plant tolerance to glyphosate have usually examined direct responses to herbicide application based on dose-response bioassays (e.g., Barroso et al 2010;Panozzo et al 2020), in which plants are typically exposed to much higher concentrations of glyphosate than those used here. Overall, our results support the previous finding that plants may be less sensitive to glyphosate residues than their associated micro-organisms (Claassens et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the application time is crucial for reaching satisfactory control with the lowest herbicide doses. On the other hand, it is well-known that besides the weed species and the growing period of the weeds, ecological conditions and weed populations [48] significantly affect the impact of herbicides. There can be important variation among the weed populations.…”
Section: Discussionmentioning
confidence: 99%
“…hold many characteristics, (i.e., high genetic diversity and ability to exchange genetic material due to gene flow) that enable them to evolve resistance mechanisms to a plethora of different herbicides. On the other hand, glyphosate is one of the most efficient post-emergence herbicides, mainly in cropping systems targeting grasses [38]. For all these reasons, advancing our knowledge on TSR and NTSR mechanisms of Lolium spp.…”
Section: Discussionmentioning
confidence: 99%